Controlled DNA condensation and targeted cellular imaging by ligand exchange in a polysaccharide–quantum dot conjugate. Issue 36 (11th April 2016) - Zhang, Yu-Hui; Zhang, Ying-Ming; Yang, Yang; Chen, Li-Xia; Liu, Yu
Abstract : A polysaccharide–quantum dots hybrid nanosystem was constructed, which could be utilized as a supramolecular nanoplatform in nucleic acid binding and selective cellular imaging. Abstract : A multicomponent supramolecular nanoparticle composed of a polysaccharide–quantum dot conjugate was successfully constructed using a ligand-exchange method, which possessed low cellular cytotoxicity and showed controlled DNA condensation and targeted cellular imaging abilities toward cancer cells.